2012
DOI: 10.1080/00224499.2012.661101
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Among Heterosexual Young Adults: The Influence of Partners' Risk Behaviors and Relationship Dynamics

Abstract: This study relies on survey (N=704) and in-depth qualitative (N = 100) interviews (Toledo Adolescent Relationship Study) to examine individual, partner, and relationship barriers and facilitators to HIV testing in a sample of young adults. Consistent with the public health goal of routine testing, nearly 40% of respondents had an HIV test within the context of their current sexual relationship, and women were significantly more likely to have tested within the current relationship than were men. For women, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 76 publications
(86 reference statements)
1
9
1
Order By: Relevance
“…This suggests a group of youth who want to be certain that their sexual practices are safe. This is in contrast with those in our study who used condoms inconsistently, the highest risk group, who had lesser intention to use HCT, suggesting they may be aware of their risk and afraid or in denial of becoming infected, knowing their status, or having AIDS, which may interfere with HCT seeking (Longmore, Johnson, Manning, & Giordano, 2012;Ober, Martino, Ewing, & Tucker, 2012).…”
Section: Discussioncontrasting
confidence: 81%
“…This suggests a group of youth who want to be certain that their sexual practices are safe. This is in contrast with those in our study who used condoms inconsistently, the highest risk group, who had lesser intention to use HCT, suggesting they may be aware of their risk and afraid or in denial of becoming infected, knowing their status, or having AIDS, which may interfere with HCT seeking (Longmore, Johnson, Manning, & Giordano, 2012;Ober, Martino, Ewing, & Tucker, 2012).…”
Section: Discussioncontrasting
confidence: 81%
“…51,54 Only one study of Ohio high school aged adolescent couples reported on relationship characteristics and found that HIV testing was associated with romantic love, but not with sexual nonexclusivity or partner's risk behaviors. 52 It makes sense that youth in serious relationships who have greater opportunity for communication about HIV/AIDS may report higher testing rates. Youth who have less committed, less serious partners or non-exclusive partners, however, may be at higher risk for HIV, and, therefore, it is discouraging that they are less likely to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28]51,52 Our study examined the roles of individual, partner, and relationship factors with HIV testing in an effort to inform high-impact interventions in minority adolescents at risk for HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been noted that relationship power plays a role in the use of sexual health services (Blanc, 2001), little research has explicitly studied the intersection of power and HIV testing. In one exception conducted in the United States, Longmore, Johnson, Manning, and Giordano (2013) found that power does play a role in young women’s ability to test for HIV such that women with higher levels of power were more likely to have tested during their relationship. In sub-Saharan Africa, the ongoing shift toward biomedical approaches to HIV and AIDS underscores the need to understand how relationship power affects use of HIV services.…”
Section: Introductionmentioning
confidence: 99%